Survivability, growth and body measurements of Awassi and TahirovaxAwassi (F1) lambs - Kul, S; Seker, I; Yildirim, O (Garuda Scientific Publications, 2006)
This study was undertaken to compare the growth rate, survivability and some body measurements of Awassi and Tahirova (75% East Friesian and 25% Kivircik) x Awassi (F,) crossbred lambs. The mean body weight of Awassi and crossbred lambs were 4.06 and 4.57 kg at birth, and 14.56 and 19.17 kg (P < 0.05) at weaning, respectively. The average survivability until weaning were 90.00% and 78.95% (P < 0.01), respectively. The body length of Awassi and crossbred lambs were 64.11 and 66.17 cm, withers height 63.67 and 59.67 cm, pelvic width 23.11 and 25.83 cm (P < 0.05), chest circumference 97.89 and 82.00 cm (P < 0. 01), leg height 34. 00 and 31.17 cm (P < 0. 01), respectively. It may be concluded that Tahirova x Awassi (F) lambs had higher body weight but lower survivability especially during weaning period as compared to Awassi lambs.
Keywords: East Friesian; Awassi; Tahirova; crossbreeding; growth; body measurements; survivability